2022
DOI: 10.1055/s-0042-1758563
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in amyotrophic lateral sclerosis and correlated factors

Abstract: Background Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease that leads to muscle weakness and paralysis. Fatigue is a disabling symptom, frequently reported in ALS, but remains under-investigated in this population. Thus, an accurate investigation of this symptom and possible associated factors in this clinical condition is needed to assist in the establishment of an adequate treatment approach. Objective To investigate the presence of fatigue in individuals with ALS and possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 26 publications
(89 reference statements)
1
9
0
Order By: Relevance
“…As shown in Table 3 , fatigue was associated with lower functional status and poorer quality of life (QoL) and well-being of patients with ALS across the included studies. Four studies reported a negative correlation between fatigue and ALSFRS-R [ 9 , 37 , 40 , 41 ], while two studies found a positive correlation between fatigue and depression [ 9 , 40 ]. Furthermore, our meta-regression confirmed the negative association between fatigue and ALSFRS-R mean ( P = 0.02), as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 3 , fatigue was associated with lower functional status and poorer quality of life (QoL) and well-being of patients with ALS across the included studies. Four studies reported a negative correlation between fatigue and ALSFRS-R [ 9 , 37 , 40 , 41 ], while two studies found a positive correlation between fatigue and depression [ 9 , 40 ]. Furthermore, our meta-regression confirmed the negative association between fatigue and ALSFRS-R mean ( P = 0.02), as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, our analysis revealed a significant association between lower ALSFRS-R scores and fatigue in ALS patients. This association may be attributed to less functionality, lower QoL, higher levels of pain, more advanced disease progression, and more pronounced muscle weakness, as discussed in the study conducted by Alencar et al [ 37 ].…”
Section: Discussionmentioning
confidence: 98%
“…Fatigue is a largely overlooked clinical concern in ALS, often evading the notice of healthcare professionals who provide care for individuals with ALS. Nonetheless, it is very important to assess this non-motor symptom in ALS patients, since it can seriously lower the QoL of the patients [115][116][117]. In ALS, both central and peripheral fatigue play a significant role.…”
Section: Fatiguementioning
confidence: 99%
“…Fatigue exhibits a negative association with the ALSFRS-R score [115,[120][121][122][123]. Hamad et al proposed that this correlation may be attributed to reduced functionality, diminished QoL, higher pain levels, advanced disease progression, and muscle weakness [119].…”
Section: Factors Associated With Fatigue In Als Patientsmentioning
confidence: 99%
See 1 more Smart Citation